Pengaruh Gaya Kepemimpinan Terhadap Kinerja Pengurus KONI Kabupaten Sukabumi - Siti Rahayu; Umban Adi Jaya (Institut Manajemen Wiyata Indonesia, 2021)
Leaders have a very decisive role in achieving success and failure in achieving organizational goals. This study aims to determine the effect of leadership style on the performance of KONI officials in Sukabumi Regency. The research approach used is quantitative associative. Research subjects or respondents amounted to 31 people. The research instrument is a questionnaire with 20 statement items. The results showed that leadership style had no effect on the performance of KONI officials in Sukabumi Regency. Based on the respondents' responses, it was found that in a certain situation the leadership style was able to influence the performance of the management for the better, but in general or overall the effect was not significant.